Pengetahuan Dengan Keterampilan Praktek Asuhan Kebidanan Antenatal Care Pada Mahasiswa Semester IV (Empat) DIII Kebidanan Fakultas Ilmu Kesehatan Universitas Respati Indonesia. - Triana, Ani (Jurnal Martenity and Neonatal, 2015)
Midwifery students are candidates or embryo midwife who has the knowledge and professional skills and the quality of education obtained through a midwife for 3 years at the college level. Of the data value of midwifery care I (in pregnant women) and the value of student clinical practice DIII Midwifery Faculty of Health Sciences University of Indonesia Respati there is a gap between the knowledge with their skills because of the number of students is about 54 people to value their practice skills got a C and D as 39 people. The purpose of this study was to determine the relationship of knowledge to the practice of midwifery care skills antenatal care in the fourth semester students Midwifery Diploma Respati Faculty of Health Sciences University of Indonesia in 2009, includes anamnesis, clinical examination, laboratory examination and diagnosis. This is design research with cross sectional study and sampel equals 54 respondent. The analysis used is Chi Square test. Results of research have variabels a significant relationship with the practice of midwifery care skills antenatal care is the clinical examination (p = 0.007), laboratory tests (p = 0.009), diagnosis (p = 0.002).